INTEGRATING STEAM AND EDUPRENEURSHIP IN PRIMARY EDUCATION TO IMPROVE SCIENCE LITERACY AND STUDENT CREATIVITY - Trivena; Benyamin Salu; Grifit Markus (Jurnal Cakrawala Pendas, 2025)
21st-century learning demands the early integration of critical thinking, creativity, and entrepreneurial skills. The STEAM approach offers interdisciplinary and contextual learning, yet it still requires a stronger connection to students’ real-life experiences. Integrating STEAM with edupreneurship presents an innovative solution to enhance scientific literacy and creativity among elementary school students. This study aims to examine the effectiveness of integrating the STEAM (Science, Technology, Engineering, Arts, and Mathematics) approach with edupreneurship in improving scientific literacy and creativity in elementary school students. The study was conducted at SDN 6 Saluputti using a descriptive qualitative approach, involving students from grades IV to VI as research subjects. Data were collected through observation, documentation, and interviews. Thematic analysis was employed to identify the impact of the integration on students’ development of scientific literacy and creativity. The applied method was project-based learning, where students were guided to create tangible products such as herbal soap, artwork from recycled materials, and digital educational posters. The findings reveal that the integration of STEAM and edupreneurship positively influences students’ scientific literacy. Students were able to understand scientific concepts contextually, conduct simple experiments, and communicate their findings logically and creatively. In terms of creativity, there was a significant improvement in four key indicators: fluency of ideas, flexibility of thought, originality, and elaboration. The products created reflected interdisciplinary thinking skills and an innovative spirit. Furthermore, students demonstrated high enthusiasm and engagement throughout the learning process. They actively participated in discussions, collaborated in groups, and expressed pride in their work. Learning became more meaningful, enjoyable, and fostered character values such as independence, responsibility, and collaboration. The integration of STEAM and edupreneurship has proven to be an effective innovative learning approach that enhances the quality of primary education, particularly in shaping a generation that is creative, scientifically literate, and entrepreneurially minded.